Malleability of uranium: Manipulating the charge-density wave in epitaxial films - Springell, R; Ward, R; Bouchet, J; Chivall, J; Wermeille, D; Normile, P; Langridge, S; Zochowski, S; Lander, G (American Physical Society, 2014)
We report x-ray synchrotron experiments on epitaxial films of uranium, deposited on niobium and tungsten seed layers. Despite similar lattice parameters for these refractory metals, the uranium epitaxial arrangements are different and the strains propagated along the orthorhombic a axis of the uranium layers are of opposite sign. At low temperatures these changes in epitaxy result in dramatic modifications to the behavior of the charge-density wave in uranium. The differences are explained with the current theory for the electron-phonon coupling in the uranium lattice. Our results emphasize the intriguing possibilities of producing epitaxial films of elements that have complex structures like the light actinides uranium to plutonium. © 2014 American Physical Society.